Features of Ethno-Linguistic Identity Characteristic for Representatives of Different Ukrainian Linguistic Groups - Eliso Hryshchuk; Alla Kovalenko (Психолінгвістика, 2019)
The article analyzes features of ethno-linguistic identity characteristic for representatives of the main Ukrainian language groups: Ukrainian-speaking Ukrainians, Russian-speaking Ukrainians and Russian-speaking Russians. The main concepts of the ethno-linguistic identity theory and ethnic group vitality are examined; individual and collective strategies maintaining positive identity through language are described; the factors influencing language expressiveness in the structure of ethnic identity are presented. The article shows that Russian-speaking Ukrainians are more competent in both languages​(Ukrainian and Russian); Ukrainian-speaking Ukrainians are highly proficient in their ethnic language and have predominantly an average level of Russian language proficiency; Russian-speaking Russians are characterized by good understanding and knowledge of their ethnic language only, at the same time they are low proficient in Ukrainian. As for Ukrainian-speaking Ukrainians and Russian-speaking Russians, their ethnic language competence coincides with their linguistic behaviour and attitudes. Russian-speaking Ukrainians do not show such coincidence; they are characterized by a discrepancy between the prevailing positive attitude to their ethnic language and their real linguistic behaviour. The data shows that the respondents do not choose mainly a language as a main ethnic-determining characteristic, however, in the system together with other distinctive features, it still occupies uppers rank positions for Ukrainian-speaking and Russian-speaking Ukrainians; family ties and psychological choices are more important for ethnic identification of Russian-speaking Russians. The vast majority of the respondents do not focus on their own ethnic status, paying more attention to personal, family and professional social characteristics. Ukrainian-speaking Ukrainians have the most steadfast ethnic identity, and marginal ethnic identity is predominantly observed among Russian-speaking Ukrainians. The relation between language and ethnic identity is described: correspondence between mother and ethnic language determines the respondents’ positive ethnic identity, and vice-versa, their mismatch leads to appearance of ethno-nihilistic tendencies.